Gene coexpression patterns during early development of the native Arabidopsis reproductive meristem: novel candidate developmental regulators and patterns of functional redundancy. (28th July 2014) - Mantegazza, Otho; Gregis, Veronica; Chiara, Matteo; Selva, Caterina; Leo, Giulia; Horner, David S.; Kater, Martin M.
Summary During very early stages of flower development in Arabidopsis thaliana, a series of key decisions are taken. Indeed, the position and the basic patterning of new flowers are determined in less than 4 days. Given that the scientific literature provides hard evidence for the function of only 10% of A. thaliana genes, we hypothesized that although many essential genes have already been identified, many poorly characterized genes are likely to be involved in floral patterning. In the current study, we use high‐throughput sequencing to describe the transcriptome of the native inflorescence meristem, the floral meristem and the new flower immediately after the start of organ differentiation. We provide evidence that our experimental system is reliable and less affected by experimental artefacts than a widely used floral induction system. Furthermore, we show how these data can be used to identify candidate genes for functional studies, and to generate hypotheses of functional redundancies and regulatory interactions.